2014
DOI: 10.1088/0264-9381/31/21/214006
|View full text |Cite
|
Sign up to set email alerts
|

Spacetime entanglement entropy in 1 + 1 dimensions

Abstract: Reference [1] defines an entropy for a gaussian scalar field φ in an arbitrary region of either a causal set or a continuous spacetime, given only the correlator φ(x)φ(y) within the region. As a first application, we compute numerically the entanglement entropy in two cases where the asymptotic form is known or suspected from conformal field theory, finding excellent agreement when the required ultraviolet cutoff is implemented as a truncation on spacetime mode-sums. We also show how the symmetry of entanglem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(77 citation statements)
references
References 17 publications
5
69
3
Order By: Relevance
“…From the definitions of the associated Legendre functions we have 18 : Let C k = D k = 0 for k = 0 19 , and A qk = B qk = 0 for k = 0 20 . We can then write A qk = δ qk cosh α k , B qk = δ qk sinh α k e iβ k , and (96)-(97) become…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the definitions of the associated Legendre functions we have 18 : Let C k = D k = 0 for k = 0 19 , and A qk = B qk = 0 for k = 0 20 . We can then write A qk = δ qk cosh α k , B qk = δ qk sinh α k e iβ k , and (96)-(97) become…”
Section: Discussionmentioning
confidence: 99%
“…Dimensional analysis tells us what are the right quantities to compare. 19 Justification for C k = D k = 0 when k = 0:…”
Section: Appendix A: De Sitter Spacetimementioning
confidence: 99%
“…To this end we need to know the von Neumann entropy of an arbitrary Gaussian density matrix, which can be expressed in terms of the correlators (8). This relation has been addressed in detail in [55], and more recently in [39,[56][57][58], where it was demonstrated that the von Neumann entropy of a Gaussian density matrix can be expressed in terms of the so-called symplectic eigenvalues of the block matrix…”
Section: A Bosonic Matrix Modelmentioning
confidence: 99%
“…Indeed, numerical simulations [17] strongly suggest that in these two cases the entanglement entropy will diverge in the absence of some sort of infrared regulator (the divergence being logarithmic in the regulator). In the analysis above, we have implicitly imposed such a regulator, for example Dirichlet conditions at one end of the spatial interval [0, L], or as in [18] the choice of "Sorkin-Johnston-vacuum" in some large "causal diamond" containing [0, L]. )…”
Section: Reasons For the Area Law And Departures From Itmentioning
confidence: 99%
“…For the purposes of condensed matter, this is not a problem, of course, but in the context of relativistic quantum field theory, or of black hole entropy, a more four-dimensional treatment would be desirable. Such a method was introduced in [20] and illustrated in [18] by a 1 + 1 dimensional calculation of entanglement entropy. Taking this as a point of reference, it would be interesting to ask whether the intuitive explanations offered above could also be cast into spatio-temporal form.…”
Section: Reasons For the Area Law And Departures From Itmentioning
confidence: 99%